2017
DOI: 10.1073/pnas.1700351114
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees return favors at a personal cost

Abstract: Humans regularly provide others with resources at a personal cost to themselves. Chimpanzees engage in some cooperative behaviors in the wild as well, but their motivational underpinnings are unclear. In three experiments, chimpanzees (Pan troglodytes) always chose between an option delivering food both to themselves and a partner and one delivering food only to themselves. In one condition, a conspecific partner had just previously taken a personal risk to make this choice available. In another condition, no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 59 publications
6
52
2
Order By: Relevance
“…However, in several studies the target objects could not be manipulated at all by the recipient since they were out of her reach [3,25,27,28]. This stimulus-enhancement hypothesis can also not explain why chimpanzees would help those A c c e p t e d M a n u s c r i p t individuals, who have helped them previously, more [38,39,40]. And lastly, the bonobo results also pose a problem for this explanation, since they help proactively, so either one believes in that a different alternative explanation would be needed for them.…”
Section: Prosociality In Chimpanzees and Bonobosmentioning
confidence: 99%
“…However, in several studies the target objects could not be manipulated at all by the recipient since they were out of her reach [3,25,27,28]. This stimulus-enhancement hypothesis can also not explain why chimpanzees would help those A c c e p t e d M a n u s c r i p t individuals, who have helped them previously, more [38,39,40]. And lastly, the bonobo results also pose a problem for this explanation, since they help proactively, so either one believes in that a different alternative explanation would be needed for them.…”
Section: Prosociality In Chimpanzees and Bonobosmentioning
confidence: 99%
“…One interesting avenue for future research is to identify the conditions under which chimpanzees are paternalistic and do correct others. Previous work has shown that chimpanzee helping behavior does increase towards conspecifics who have benefitted the individual in the past (Schmelz, Grueneisen, Kabalak, Jost, & Tomasello, ). In such scenarios of dependence chimpanzees may correct others’ dysfunctional requests for help because they themselves want to be helped by having their need rather than their request being fulfilled.…”
Section: Discussionmentioning
confidence: 99%
“…3C), while INR associated more strongly with AtSERK co-receptors after peptide treatment (Fig. 3D, 3E) Dynamic plant defense responses to herbivory have been examined for nearly 50 years (22)(23)(24) and are induced by numerous insect associated elicitors or HAMPs (3,4). Tables S1-S2…”
Section: Lrr-type Surface Receptors In Plants Typically Associate Witmentioning
confidence: 99%
“…Herbivores defoliate and often devastate plants, making effective inducible defense responses critical for plant resilience (1,2). To combat insect herbivores, plants respond to specific molecular patterns present in oral secretions (OS) and frass by amplifying wound-induced defenses and activating resistance (3,4). Analogous immune responses to microbes and other 50 pests are mediated by ligand-receptor interactions mediated by receptor kinases (RKs) or receptor-like proteins (RLPs) (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation